The effect of four sprue shapes on the quality of cobalt-chromium cast removable partial denture frame-works - M Viswambaran; S K Agarwal (Wolters Kluwer Medknow Publications, 2013)
Statement of Problem: Sprue design is a factor that controls the velocity and adequate supply of metal to the mould. Currently various manufacturers recommend different shapes of sprue, which have not been advocated in textbooks and literature is lacking for their routine applications. Purpose: This in vitro study was carried out to determine the efficacy of four sprue shapes in producing complete, void free cobalt-chrome removable partial denture frameworks. Materials and Methods: A brass metal die with a Kennedy class III, modification 1, partially edentulous arch was used and four sprue shapes (Group A-Ribbon, Group B-Square, Group C-Round and Group D- Round with reservoir) were evaluated. 40 refractory casts were made, 10 wax patterns for each sprue design were waxed up, invested with phosphate bonded investment material and castings done with induction casting machine by the same operator under standardized protocols. The cast frameworks were evaluated for 1.The defects observed visually before finishing and polishing procedures, 2. Fit on the master die as seen with naked eye and 3.Defects on radiographic evaluation. Data were tabulated and statistically analyzed with 1-way ANOVA followed by Student 't' test. Results: The results differed significantly (P < 0.0001) between the Groups with maximum defects in the castings of Group A followed in decreasing order by Group B, Group C and Group D. When comparing between the Groups (P < 0.05), the defects in Groups C and D was significantly lower than Group A and Group B. Conclusions: Round sprues with reservoir produced most satisfactory fit of castings with minimum number of internal and external defects.